FRI0005 In Early RA Patients with Non-Response to Methotrexate Monotherapy the Change in Multi-Biomarker Disease Activity Score is Differentially Associated with Subsequent Response to Non-Biological versus Biological Therapy. (10th June 2014) - Hambardzumyan, K.; Bolce, R.; Saevarsdottir, S.; Forslind, K.; Petersson, I.F.; Geborek, P.; Ernestam, S.; Sasso, E.H.; Chernoff, D.; Cruickshank, S.E.; Van Vollenhoven, R.F.
Abstract : Background: For patients with early RA (eRA), methotrexate (MTX) is recommended as first-line treatment and in non-responders both the addition of conventional non-biological disease modifying anti-rheumatic drug therapy (triple DMARD therapy) and of biological (anti-TNF) therapy are supported by data. Identification of patients with a higher likelihood of responding to one or the other of these options would lead to more personalised medicine and an increased effectiveness of therapy. Objectives: To evaluate the change in the multi-biomarker disease activity (MBDA) score during MTX therapy as a predictor of response to subsequent triple versus biological therapy. Methods: Patients with eRA and DAS28>3.2 entered the SWEFOT clinical trial and received MTX monotherapy for 3 months, at which time clinical non-responders (DAS28>3.2) were randomised to receive non-biological triple DMARD therapy (arm A) or anti-TNF (infliximab) therapy with MTX (arm B). For this study, 129 non-responders at month 3 (n=62 from arm A and n=67 from arm B) were analysed by MBDA score at baseline (BL) and month 3. The assessment of changes in the MBDA score (ΔMBDA) from BL to month 3 as a predictor for response to triple or anti-TNF therapy at year 1 was done by defining small (≤6), moderate (7-20) and large (>20) decreases by tertiles. Small and moderate decreases were combined together (small/moderate) and compared versus large decreases for arms A and B. The proportion of patients in arm A versus arm B with response at year 1 was evaluated by the odds ratio (OR) for patients with small/moderate versus large decreases. Homogeneity of the odds ratios between the two cohorts was assessed by Breslow-Day test. Results: The mean (median) decreases in MBDA score from BL to month 3 for year 1 responders (n=66) and non-responders (n=63) were 12.9 (10) and 10.8 (9), respectively (p=0.431), and month 3 mean (median) MBDA scores were 47.1 (45) and 50.3 (47), respectively (p=0.336). Patients who had small/moderate decreases in MBDA score during MTX monotherapy, 43% responded to subsequent triple therapy and 57% responded to anti-TNF (OR=0.577). In contrast, among patients with a large decreases in MBDA score from BL to month 3, 67% responded to subsequent triple therapy and 37% to anti-TNF treatment (OR=3.33). Thus the relative treatment effect of arm A versus arm B differed according to the degree of change in the MBDA score from BL to 3 months (p=0.032). Conclusions: Among patients with eRA who did not achieve low disease activity on MTX monotherapy, those patients with the greatest decreases in MDBA score were more likely to respond to triple therapy whereas patients with lesser decreases of the MBDA score were more likely to respond to anti-TNF therapy. These findings suggest that in MTX non-responders the changes in MBDA score may help guide subsequent therapy. Disclosure of Interest: K. Hambardzumyan: None declared, R. Bolce Shareholder of: Crescendo Bioscience, Employee of: Crescendo Bioscience, S. Saevarsdottir: None declared, K. Forslind: None declared, I. Petersson Speakers bureau: UCB Pharma, Pfizer, AbbVie, P. Geborek: None declared, S. Ernestam: None declared, E. Sasso Shareholder of: Crescendo Bioscience, Employee of: Crescendo Bioscience, D. Chernoff Shareholder of: Crescendo Bioscience, Consultant for: Crescendo Bioscience, S. Cruickshank Consultant for: Crescendo Bioscience, R. Van Vollenhoven Grant/research support: Abb Vie, BMS, GSK, Pfizer, Roche, UCB, Consultant for: AbbVie, Biotest, BMS, Crescendo Bioscience, GSK, Janssen, Lilly, Merck, Pfizer, Roche, UCB, Vertex DOI: 10.1136/annrheumdis-2014-eular.4231